RESPON PRIMATA TERHADAP KEHADIRAN MANUSIA DI KAWASAN CIKANIKI, TAMAN NASIONAL GUNUNG HALIMUN - Tobing, Imran Said L (BERITA BIOLOGI, 2002)
The arrival of human und their activities on protected areas will be a problem causing habitat degradation in quality due to cutting of trees,hunting and noising.This research was conducted to observe the difference of responses of primates to the arrival of human on disturbed and undisturbed forest in Cikaniki area,Mount Halimun National Park. Primates responses to environmental changes will be detected from vigilance behaviour in the form of early detection and reactions.The results of this research indicated that the three species of primates in Cikaniki area (javan gibbon, javan langur, and grizzled langur) generally detected early to the observers arrival compared to the observer himself detecting the position of primates.The early detection of the three species of primates is slower in disturbed forest compared to the undisturbed one.Furthermore,the reactions of these three species generally negative;although sometimes they response neutrally, but none was positive response in both disturbed and undisturbed forest. This behaviour indicated that although the primates have been adapted to the presence of human (early detection: slower in disturbed forest), but they still vigilant to the presence of human with negative responses.